PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN TALAOK BAYANG - Ningsih, Fitri Yulia; Anggraini, Villia; Mardiyah, Ainil (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research is motivated by the students understanding of mathematical concepts are still low and the students did not dare to ask and did not want to answer questions from the teacher. This study aimed to determine whether students understanding of mathematical concepts by implementing cooperative learning model exchanging greetings and questions technique better understanding of mathematical concepts than students taught with conventional teaching. This research is an experimental study, the research design Against Random subject. The instrument used in this study is the ultimate test of understanding of mathematical concepts. Based on the results of the analysis of the data found that both classes of normally distributed and homogeneous samples. Hypothesis test results obtained t = 1,86 and is larger than the table = 1,665 thus reject H0 which means thank H1, the hypothesis in this study received and it can be concluded that the students understanding of mathematical concepts by implementing cooperative learning techniques about exchanging greetings and more understanding of mathematical concepts better than students taught by conventional teaching eighth grade students MTsN Talaok shadow.Â